The Influence of Peers on Students’ Truancy Behavior - Labaona, Yohanista Bibiana Ose; Dhiu, Margaretha (The Future of Education Journal, 2025)
Truancy is one of the most common forms of school delinquency found among students and can negatively affect academic achievement, discipline, and adolescent social development. One of the major factors influencing this behavior is peer influence, which plays a significant role in shaping students’ decisions and actions. This study aims to examine how peer groups contribute to strengthening or encouraging truancy among secondary school students. This research employs a descriptive qualitative approach to explore the dynamics of peer relationships, forms of social pressure, and interaction patterns that influence students to skip classes without permission. The findings indicate that peers have a significant effect through invitations, group pressure, the need for acceptance, and collective habits that contradict school rules. Furthermore, unhealthy peer relationships may weaken students’ self-control, making them more susceptible to violating school regulations. Therefore, active involvement from teachers, counselors, and the school environment is needed to reinforce positive values and build peer groups that support disciplined behavior.